Fluorescent Mechanism and Optical Switching of Fluorophore‐Free Organogel. Issue 5 (6th November 2022) - Liang, Shumin; Zhang, Lidong
Abstract: Fluorophore is essential to enable the fluorescence and optical switching in most of polymer gels. Herein, a novel concept is proposed to develop a fluorophore‐free organogel that is capable of generation of blue fluorescence at transparent state, while it proceeds with optical switching from blue to purple upon phase transition into non‐transparent state in water. Ammonium persulphate (APS) is utilized to initiate co‐crosslinking of hydrophilic acrylamide (AM) and hydrophobic 2, 2, 3, 4, 4, 4‐hexafluorobutyl acrylate (HFBA) in dimethyl sulphoxide (DMSO) to give organogel of AM@HFBA at 80 °C. APS decomposes to generate not only radicals, but also ammonium bisulfate (ABS) during heating, in which the elements of ABS produce blue fluorescence ( λ  = 440 nm), excited by UV light ( λ  = 365 nm). After the phase transition into non‐transparent state, light‐reflection behavior at the phase‐transitioned surface triggers the optical switching of the organogel from blue to purple under UV light. The optical switching is patternable and reversible, which enables the applications of organogel of AM@HFBA for information encoding/encryption and optical‐switchable soft actuators. This method is universal to achieve fluorescence and optical switching for free radical polymerization‐based gel systems as long as they are initiated by APS in DMSO. Abstract : Fluorophore is essential to enable the fluorescence and optical switching in most of polymer gels. Here, a novel concept is proposed to develop a fluorophore‐free organogel that is capable of generation of blue fluorescence at transparent state, while it proceeds with optical switching from blue to purple upon phase transition into non‐transparent state in water.